The family as a source of social support for patients with colostomy - Leyk, Magdalena; Książek, Janina; Stangiewicz, Michał (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Exposing colostomy is connected with a considerable fall of patient’s quality of life. Social support plays an important role in patient’s adaptation to a new life situation. Family is perceived as one of the most fundamental sources of support. Aim of the study. Subjective assessment of family’s role in giving social support to the patients with colostomy. Material and methods. The research group contained 128 persons with colostomy. In the research the method of diagnostic survey and statistic method were used. The social support was assessed with the Berlin Social Support Scale. Results. The results prove that the level of social support diminishes with time that has passed from the moment of creating colostomy. The time has also influence on the fall of the level of patient’s satisfaction with the received support. The level of demand for the support is constant throughout the whole period of illness. The patients receive much more support than they really expect. Conclusions. The process of support given by family should be permanent and be given throughout the whole rest of patient’s life. The level of the support should be adjusted to the patient’s expectation in terms of quantity and quality. Nursing Topics 2010; 18 (1): 41-46